Analisis Perencanaan Pembelajaran Guru Ekonomi Kelas XI di SMA Negeri 11 Ambon - Wabula, Fitri Andriyani; Rehalat, Aminah; Ubra, Franklin William (Universitas Pattimura, 2023)
The quality of lesson planning by teachers is a crucial factor in enhancing the effectiveness of the teaching and learning process at schools. This study aims to analyze the extent to which grade XI economics teachers at SMA Negeri 11 Ambon are able to design lesson plans that align with educational standards. The research employed a qualitative descriptive method by analyzing syllabus and lesson plan documents prepared by the economics teacher. The assessment was based on six main indicators: determining learning objectives, developing materials and media, organizing learning scenarios, managing the classroom, planning assessments, and document presentation. The results showed that the teacher was able to design lesson plans well, as indicated by the average score that nearly reached the “very good” category. These findings highlight the importance of lesson planning skills in supporting the effective achievement of learning objectives. The implication is that teachers should receive ongoing training and regular evaluations so that the quality of lesson planning continues to improve and can serve as a model of best practice for other schools